Automultiscopic displays based on orbital angular momentum of light. (20th July 2016) - Li, Xuefeng; Chu, Jiaqi; Smithwick, Quinn; Chu, Daping
Abstract: Orbital angular momentum (OAM) of light has drawn increasing attention due to its intriguingly rich physics and potential for a variety of applications. Having an unbounded set of orthogonal states, OAM has been used to enhance the channel capacity of data transmission. We propose and demonstrate the viability of using OAM to create an automultiscopic 3D display. Multi-view image information is encoded using an OAM beam array, then sorted into different view directions using coordinate transformation elements. A three-view demonstration was achieved to encode and decode 9 × 9 pixel images. These demonstrations suggest that OAM could potentially serve as an additional platform for future 3D display systems.